Contemporary issues in Islam - Afsaruddin, Asma, 1958- (New Edinburgh Islamic surveys., 2015)
This book deals with certain ""hot-button"" contemporary issues in Islam that are often the focus of public scrutiny, including the Sharia, jihad, the caliphate, women's status, and interfaith relations. Notably, it places the discussion of these topics within a longer historical framework in order to reveal their multiple interpretations and contested applications over time. Most public and some academic discourses however present the Islamic tradition as unchanging and therefore unable to respond to the modern world. Such an ahistorical approach fosters the belief that Muslim and Western soc